Inquiry slides for developing science process skills in high school biology - De Guzman, Rosario E. (1978)
This study constructed and validated a set of inquiry slides for teaching plant growth regulation and developing science process skills such as analyzing, interpreting and relating the results of experiments. Trial sessions using the slides and the teacher's guide were held at the Manila Science High School involving 114 students to obtain feedback for the refinement of the slides and the teacher's guide as well as to determine their effectiveness. Reactions were obtained through the use of questionnaires. These indicate the students' appreciation of the slides' interesting and challenging aspects and showed that the students felt that the slides improved their ability to analyze, interpret, and relate the experimental results. The teachers' observation also supported the students' responses that the slides encouraged active paricipation in class. The slides were considered more effective than lectures in presenting science lessons. The use of more inquiry slides in Biology in the future was recommended.
Thesis (M.A. Biology Education)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Philippines -- Manila